Associations of aged neutrophils with disease activity in primary Sjögren's syndrome - Lei Han; Chunyuan Xiao; Tianlin Lu; Xinfang Huang (Rheumatology & Autoimmunity)
Abstract Background Primary Sjögren's syndrome (pSS) is a chronic autoimmune disease that primarily affects exocrine glands. This study aimed to investigate the correlation between aged neutrophils and disease activity in patients with pSS. Methods This study included 21 patients diagnosed with pSS and 32 healthy controls (HCs) at Shanghai East Hospital between September 2021 and May 2023. Peripheral blood samples were collected from them. Neutrophil subsets were identified using cell surface markers (CD62L, CXCR4, CD11b, and CXCR1) and analyzed using flow cytometry. Clinical data, including the European League Against Rheumatism Sjögren's Syndrome Disease Activity Index (ESSDAI) and serum ferritin levels, were also collected at admission. Results Serum ferritin levels were associated with the ESSDAI and neutrophil‐to‐lymphocyte ratio in patients with pSS. Our study revealed a significant increase in the frequency of aged neutrophils in patients with pSS compared to HCs (p < 0.05). The frequency of aged neutrophils significantly correlated with ESSDAI and ferritin levels in patients with pSS (p < 0.05). We generated a receiver operating characteristic (ROC) curve to evaluate the diagnostic utility of aged neutrophils in pSS. ROC analysis showed an area under the curve of 0.8036, with a p‐value of 0.0002. Conclusions This study confirmed that patients with pSS exhibit a higher percentage of aged neutrophils. Furthermore, aged neutrophils may serve as diagnostic markers of pSS.